Comparison of Glucocorticoid and Nonsteroidal Anti-Inflammatory Drug Requirement Before and After Tumor Necrosis Factor Inhibitor Treatment in Patients With Rheumatoid Arthritis - Merih BİRLİK,; Sedat ÇAPAR,; Servet AKAR,; İsmail SARI,; Fatos ÖNEN,; Nurullah AKKOÇ, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate whether use of nonsteroidal anti-inflammatory drugs (NSAIDs) or glucocorticoids (GCs) decreases over different time intervals before and after anti-tumor necrosis factor (anti-TNF) therapy in rheumatoid arthritis (RA) patients. Patients and methods: Data were extracted from electronic prescription records of the Pension Fund of Turkey covering records from the years 2000 to 2005 to detect patients aged 18 years or older who were administered anti-TNF agents. All TNF blockers, NSAIDs and GCs which were available in the market were our target of investigation. Patients were categorized into three groups defined by duration of continuous anti-TNF use (episode-1: >90 days, episode-2: >180 days, episode-3: >365 days). First anti-TNF prescription detected in the database was identified as the index prescription and its date was taken as the start date of therapy. GC and NSAID consumptions during the first three, six and 12 months before initiation of anti-TNF agents were compared with the subsequent same duration of consumptions after the initiation of anti-TNF agents. Results: Comparison of GC consumptions in each paired-durations of six and 12 months before and after anti-TNF therapy revealed significantly decreased mean daily GC intake. Achieved reduction rates were 11% at six months and 30% at 12 months. Initiation of anti-TNF therapy was found to be associated with reduced NSAID use. This pattern was similar as that of GC use except for consumption comparisons in the first episode. Conclusion: Anti-TNF treatment reduced NSAID and GC usage in patients with RA. Evidence of decreased consumption for both medication groups have been reached statistical significance after the first six months of biologic treatment initiation.